2.5x-3(x+1)=12

Simple and best practice solution for 2.5x-3(x+1)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.5x-3(x+1)=12 equation:


Simplifying
2.5x + -3(x + 1) = 12

Reorder the terms:
2.5x + -3(1 + x) = 12
2.5x + (1 * -3 + x * -3) = 12
2.5x + (-3 + -3x) = 12

Reorder the terms:
-3 + 2.5x + -3x = 12

Combine like terms: 2.5x + -3x = -0.5x
-3 + -0.5x = 12

Solving
-3 + -0.5x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -0.5x = 12 + 3

Combine like terms: -3 + 3 = 0
0 + -0.5x = 12 + 3
-0.5x = 12 + 3

Combine like terms: 12 + 3 = 15
-0.5x = 15

Divide each side by '-0.5'.
x = -30

Simplifying
x = -30

See similar equations:

| 4x^9n+4=256 | | -70+15y+2y=-2 | | 3/9y-5=-2 | | h=15-8 | | (-5)+(-7.1)= | | 8=-9x+3 | | 4x(5x+3)=2x(7x+6) | | ((60-61)/n)x100=60 | | [-14]= | | a+3b=30 | | 6x+2=8x-12 | | (4n-3)(2n+1)=7 | | 2a+7=23 | | -1/2=2/3v-2/7 | | 2a+12=48 | | 0.25x+24=9 | | 4w+z=5 | | 114.88+-29.36= | | 114.88+-29.36=85.52 | | 7w^2+3=10w | | 2u+2=5u-16 | | 10/7=4/r | | 21-7=d | | 8/5=12/a | | -17+x=x+27 | | 8/5=122/a | | 4(4x+2)=20x+7-4x+1 | | g=12+7 | | 4/7*(-1/8) | | 40=4/5v | | 4b-10=150 | | 2L+8=140 |

Equations solver categories